THE YOUNG LEARNERS’ PERCEPTION TOWARDS ENGLISH INSTRUCTIONAL PRACTICES USING VIRTUAL PLATFORMS - Purwanti Taman; Sukma Septian Nasution; Tommy Hastomo; Nur Najibah Sukmawati; Laksmy Ady Kusumoriny (JOALL (Journal of Applied Linguistics and Literature), 2021)
The popularity of virtual-learning platforms as an alternative for instructional practices during the pandemic is rocketing yet students’ perceptions to the implementation are not optimally gauged especially to young learners. This study explores the students’ perception towards learning English using two popular virtual platforms during Covid-19 pandemic. This is a case study involving 30 students in their third-year study at a private primary-school primary school in Tangerang City, Banten. Interviewing and observing all students respectively were conducted to obtain the data needed. Using descriptive analysis, it was found that the students showed negative perceptions towards the online-based learning process. Not only the media but also the whole learning process was negatively impacted. This is a voice that highlights the issue of recent education is facing. Further studies are therefore suggested to delve into effective and feasible solutions to eradicate the negative perception because the best time to return to classroom-situated instructions remains arguable for no-exact time